The Norwegian PROMIS-29: psychometric validation in the general population for Norway - Andrew M. Garratt; Joël Coste; Alexandra Rouquette; José M. Valderas (SpringerOpen, 2021)
Abstract Background The Patient Reported Outcome Measurement Information System profile instruments include "high information" items drawn from large item banks following the application of modern psychometric criteria. The shortest adult profile, PROMIS-29, looks set to replace existing short-form instruments in research and clinical practice. The objective of this study was to undertake the first psychometric evaluation of the Norwegian PROMIS-29, following a postal survey of a random sample of 12,790 Norwegians identified through the National Registry of the Norwegian Tax Administration. Confirmatory factor analysis was used to assess structural validity. Fit to the Rasch partial credit model and differential item functioning (DIF) were assessed in relation to age, gender, and education. PROMIS-29 scores were compared to those for the EQ-5D-5L and the Self-assessed Comorbidity Questionnaire (SCQ), for purposes of assessing validity based on a priori hypotheses. Results There were 3200 (25.9%) respondents with a mean age (SD) of 51 (20.7, range 18 to 97 years) and 55% were female. The PROMIS-29 showed satisfactory structural validity and acceptable fit to Rasch model including unidimensionality, and measurement invariance across age and education levels. One pain interference item had uniform DIF for gender but splitting gave satisfactory fit. Domain reliability estimates ranged from 0.85 to 0.95. Correlations between PROMIS-29 domain, SCQ and EQ-5D scores were largely as expected, the largest being for scores assessing very similar aspects of health. Conclusions The Norwegian version of the PROMIS-29 is a reliable and valid generic self-reported measure of health in the Norwegian general population. The instrument is recommended for further application, but the analysis should be replicated and responsiveness to change assessed in future studies before it can be recommended for clinical and health services evaluation in Norway.